NURSING INTERVENTIONS HEMODIALY PATIENT I: NTEGRATIVE REVIEW (CIPEEX, 2022)
INTRODUCTION: CHRONIC RENAL INSUFFICIENCY (CRF) CONSISTS OF THE IRREVERSIBLE LOSS OF RENAL FUNCTION IN A SLOW AND PROGRESSIVE WAY. RENAL REPLACEMENT THERAPY, SUCH AS HEMODIALYSIS, PARTIALLY ALLEVIATES THE SYMPTOMS NOTED BY THE CHRONIC RENAL PATIENT. THE NURSE SHOULD BE PRESENT AT THE HEMODIALYSIS SESSIONS TO COORDINATE THE TEAM AND IDENTIFY THE CHARACTERISTICS OF EACH PATIENT. IN ADDITION, IT IS NECESSARY TO EDUCATE THE FAMILY AND THE CLIENT ABOUT THE DISEASE AND ITS COMPLICATIONS. OBJECTIVE: THIS STUDY AIMED TO DESCRIBE THE ACTIONS DEVELOPED BY THE NURSING TEAM REGARDING PATIENTS WHO UNDERGO HEMODIALYSIS TREATMENT. METHODOLOGY: THIS STUDY IS AN INTEGRATIVE REVIEW RESEARCH, BEING DEVELOPED ACCORDING TO THE SIX STAGES OF MENDES, SILVEIRA AND GALVƑO (2008). THE SELECTION OF THE ARTICLES OCCURRED THROUGH THE INTEGRATED SEARCH OF THE DESCRIPTORS MENTIONED ABOVE IN SCIELO AND VHL. AFTER THE SELECTION OF ARTICLES ACCORDING TO THE CRITERIA ESTABLISHED AND THE CRITICAL READING OF THE TEXTS IN FULL, 19 ARTICLES WERE CHOSEN. RESULTS: IN THIS INVESTIGATION, THE RESULTS WILL BE PRESENTED IN THREE CATEGORIES NAMELY: CATEGORY 1: NURSING PROCESS TO THE HEMODYNAMIC PATIENT; CATEGORY 2: ROLE OF NURSES IN RELATION TO HEMODIALYSIS COMPLICATIONS AND CATEGORY 3: QUALITY OF LIFE OF HEMODIALYSIS PATIENTS. IT CAN BE SEEN THAT NURSES PLAY A SIGNIFICANT ROLE IN CARING FOR THE PATIENT, BOTH DURING THE DURATION OF THE SESSIONS AND AFTER THEIR COMPLETION, TAKING INTO ACCOUNT THE INDIVIDUALITY OF EACH ONE. CONCLUSION: THE ACTIONS OF NURSES AND THEIR STAFF HAVE PROVED TO BE VERY SUBJECTIVE, SINCE IN ADDITION TO THEORETICAL-PRACTICAL KNOWLEDGE, NURSES MUST PERFORM THE APPROPRIATE INTERVENTIONS IN FRONT OF THE PATIENT, RESPECTING THE LEVEL OF THEIR COMPLEXITY AND NEED. SPECIFICALLY, THE NURSE IS IMPORTANT IN EXPLAINING, GUIDING AND MOTIVATING THE CLIENT AND HIS / HER FAMILY IN RELATION TO THE DISEASE, THE TREATMENT AND ITS POSSIBLE COMPLICATIONS, THUS MINIMIZING UNNECESSARY DISCOMFORTS AND DISCOMFORTS.
Keywords: Chronic Renal Insufficiency; Hemodialysis; Nursing; Quality of life.